2020
DOI: 10.1002/ldr.3724
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil evolution on the heavy metal risk in three kinds of intertidal zone of the Pearl River Estuary

Abstract: Human activities and the increasing emphasis on coastal protection contribute to the diversity and evolution of intertidal soil. But, less is known about the influence of soil evolution on the heavy metal risk in intertidal zones. In this study, soil samples were collected from three kinds of intertidal zone in the Pearl River Estuary, including bare beach (BB), a spartina growing area (SGA), and a mangrove growing area (MGA), to reveal the influence of key factors on the heavy metal risk. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 57 publications
(129 reference statements)
0
2
0
Order By: Relevance
“…These results indicate that I geo values are only related to the total concentration of heavy metals based on selected background values and did not be affected by sediment properties [42]. However, sediment properties and composition can influence the availability of heavy metals in sediments and thus affect the risk assessment [43]. In addition, the risk values of heavy metals with the same content may differ due to the different background values for each type [44].…”
Section: Effect Of Background Values On Risk Assessmentmentioning
confidence: 84%
See 1 more Smart Citation
“…These results indicate that I geo values are only related to the total concentration of heavy metals based on selected background values and did not be affected by sediment properties [42]. However, sediment properties and composition can influence the availability of heavy metals in sediments and thus affect the risk assessment [43]. In addition, the risk values of heavy metals with the same content may differ due to the different background values for each type [44].…”
Section: Effect Of Background Values On Risk Assessmentmentioning
confidence: 84%
“…The reason may be that Cu, Zn, As, Cd, and Pb mainly come from anthropogenic sources, such as the discharge of industrial wastewater and domestic sewage, which leads to serious heavy metal pollution with extremely high toxicity to local organisms [2,50]. On the contrary, Cr, Ni, and Hg mainly come from natural sources, and the influence of sediment characteristics cannot be ignored [43,51]. Meanwhile, the results also indicated that the three indicators have similar effects.…”
Section: Effect Of Sqg Values On Risk Assessmentmentioning
confidence: 99%